The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1038/ijo.2011.279
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the NADPH oxidase 4 predisposes towards diet-induced obesity

Abstract: OBJECTIVE: NADPH oxidase 4 (NOX4) is a reactive oxygen species (ROS) producing NADPH oxidase that regulates redox homeostasis in diverse insulin-sensitive cell types. In particular, NOX4-derived ROS is a key modulator of adipocyte differentiation and mediates insulin receptor signaling in mature adipocytes in vitro. Our study was aimed at investigating the role of NOX4 in adipose tissue differentiation, whole body metabolic homeostasis and insulin sensitivity in vivo. DESIGN: Mice with genetic ablation of NOX4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 56 publications
4
59
4
1
Order By: Relevance
“…Recent studies of male NOX4-deficient mice in vivo have demonstrated a phenotype contradictory to in vitro studies of insulin-dependent adipogenesis. These mice are highly susceptible to high fat-driven obesity and steatosis and have reduced adipocyte differentiation and increased energy efficiency (21). This phenotype is the opposite of that displayed by female p47phox knockout mice in the current study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Recent studies of male NOX4-deficient mice in vivo have demonstrated a phenotype contradictory to in vitro studies of insulin-dependent adipogenesis. These mice are highly susceptible to high fat-driven obesity and steatosis and have reduced adipocyte differentiation and increased energy efficiency (21). This phenotype is the opposite of that displayed by female p47phox knockout mice in the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…However, more recent in vivo studies in NOX4-deficient male mice have demonstrated increased whole body energy efficiency and predisposition toward diet-induced obesity, insulin resistance, adipose tissue inflammation, and hepatic steatosis (21). These data suggest NOX4 is actually an antiadipogenic master regulator of metabolic homeostasis and that its upregulation in obese adipose tissue might represent a defensive mechanism to limit adipose tissue expansion (21). In contrast, less is known with regard to the role of NOX2 in adipogenesis and obesity.…”
mentioning
confidence: 99%
“…Indeed, cell culture data indicate that many of the free radical-based pathways involved in adipocyte insulin sensitivity and proliferation may be mediated by NOX4 rather than NOX2 (57,81). However, in contrast to the protective effects of NOX2 deletion reported here, NOX4-deficient mice have recently been shown to have enhanced susceptibility to diet-induced obesity, with accelerated insulin resistance, enhanced adipocyte hypertrophy, and increased adipose tissue hypoxia, inflammation and apoptosis (54). These findings thus suggest differential roles for the NADPH oxidase subunits in adipose tissue, with NOX4 involved in maintaining physiological events such as insulin receptor signaling and adipocyte proliferation/differentiation, and NOX2 driving sustained inflammatory changes in response to stimuli like fatty acids or oxidized lipoproteins.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous studies have observed that increased oxidative stress promotes peripheral insulin resistance [11], and that systemic reduction of ROS/advanced glycation end products/NOX activity reduces insulin resistance [36][37][38][39][40][41][42]. The reason for the presently observed lack of effect of GLX351322 on peripheral insulin sensitivity is not known, but might relate to the isoform selectivity of GLX351322 as a NOX inhibitor or the level of ROS inhibition and/or expression of NOX enzymes in peripheral target tissues as compared to pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%